From nanostructures to nanosensing applications = Dalle nanostrutture alle applicazioni nanosensoriali - D'Amico, A. (Arnaldo), 1940-; Paoletti, A.; Balestrino, G. (Giuseppe) (Proceedings of the International School of Physics "Enrico Fermi", 2005)
Nanoscience and Nanotechnologies have grown increasingly fast for the last 20 years - after a somehow slow start - with an exceptional impact upon understanding of Nature, development of Science and related applications. Several new materials have been built and the possibility of tailoring their properties for particular purposes has opened unexpected perspectives in a multidisciplinary scenario. Furthermore, economy has also been deeply involved in this effort as a consequence of the fact that a significant amount of money has been invested in new enterprises with the hope of duplicating the.